2020
DOI: 10.1093/plphys/kiaa016
|View full text |Cite
|
Sign up to set email alerts
|

PHO1 family members transport phosphate from infected nodule cells to bacteroids inMedicago truncatula

Abstract: Legumes play an important role in the soil nitrogen availability via symbiotic nitrogen fixation (SNF). Phosphate (Pi) deficiency severely impacts SNF because of the high Pi requirement of symbiosis. Whereas PHT1 transporters are involved in Pi uptake into nodules, it is unknown how Pi is transferred from the plant infected cells to nitrogen-fixing bacteroids. We hypothesized that Medicago truncatula genes homologous to Arabidopsis PHO1, encoding a vascular apoplastic Pi exporter, are involved in Pi transfer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…We found that the expression of genes encoding Fe 2+ -, Mn 2+ , and K + transporters was significantly diminished in PvAGO5 -RNAi mature nodules ( Supplementary Figure 5 ). We also observed that the expression of Phvul.007g275300.1 that encodes the PHO1 transporter, which is required to transfer phosphate from infected nodule cells to bacteroids ( Nguyen et al., 2021 ), was significantly downregulated. In contrast, genes encoding different ABC and MATE transporter family members, as well as sugars- and amino acid- transporters, were upregulated.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We found that the expression of genes encoding Fe 2+ -, Mn 2+ , and K + transporters was significantly diminished in PvAGO5 -RNAi mature nodules ( Supplementary Figure 5 ). We also observed that the expression of Phvul.007g275300.1 that encodes the PHO1 transporter, which is required to transfer phosphate from infected nodule cells to bacteroids ( Nguyen et al., 2021 ), was significantly downregulated. In contrast, genes encoding different ABC and MATE transporter family members, as well as sugars- and amino acid- transporters, were upregulated.…”
Section: Resultsmentioning
confidence: 82%
“…Effective root nodule symbiosis depends on efficient nutrient exchange. Recent studies indicate that the Phosphate Transporter1.1 (PHO1.1) and PHO1.2 translocate phosphate from the infected cell to nitrogen-fixing bacteroids in M. truncatula ( Nguyen et al., 2021 ). Similarly, different types of iron transporters, among them Yellow Stripe-Like and Vacuolar Iron Transporter Like, aid the translocation of iron from infected nodule cells to nitrogen-fixing bacteria ( Liu et al., 2020 ; Castro-Rodríguez et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GmPAP12 is directly activated by GmPHR1 under Pi starvation conditions to maintain Pi homeostasis and nitrogen fixation (Wang et al, 2020). The vascular apoplastic Pi exporters MtPHO1.1 and MtPHO1.2, which are broadly expressed in nodules, function in Pi transport from infected nodule cells to bacteroids (Nguyen et al, 2021). SPX proteins (named after the Saccharomyces cerevisiae SYG1 and Pho81, and mammalian Xpr1) function as phosphate sensors and negatively regulate the binding affinity of PHRs.…”
Section: Introductionmentioning
confidence: 99%
“…In rice, PHO1s are also expressed at the vasculature of the uppermost node connecting to the panicle and in developing seed tissues, where they are involved in the allocation of Pi during grain filling ( Che et al, 2020 ; Ma et al, 2021) . In Medicago ( Medicago truncatula ), PHO1 mediates the transfer of Pi from nodule infected cells to bacteroids ( Nguyen et al, 2021 ). Negative regulations of Arabidopsis PHO1 either by WRKY6 at the transcriptional level ( Chen et al, 2009 ) or by its upstream open-reading frame at the translational level ( Reis et al, 2020 ) were reported.…”
Section: Introductionmentioning
confidence: 99%